The impact of routines on emotional and behavioural difficulties in children and on parental anxiety during COVID-19 - Lees, Vera; Hay, Rosie; Bould, Helen; Kwong, Alex S. F.; Major-Smith, Daniel; Kounali, Daphne; Pearson, Rebecca M. (Frontiers in Child and Adolescent Psychiatry, 2023)
Background The Covid-19 pandemic and related public health measures, including lockdowns and school closures, have impacted on mental health of children. Aims and hypothesis We hypothesised that there would be an association between maintaining a routine during lockdown and both lower emotional and behavioural difficulties in children and lower parental anxiety. Routine was taken as keeping to the same basic activities such as mealtimes and bedtimes. We also hypothesised that children of ‘keyworker’ parents would have fewer emotional and behavioural symptoms due to having maintained more normal routines. The key reason was that children of keyworkers still attended school or nursery and parents would have been getting up and coming home at the same times as pre-Covid. Keyworker status was defined as those whose work was essential to Covid-19 response, including work in health and social care and other key sectors. Methods We used data from the Avon Longitudinal Study of Parents and Children (ALSPAC) to explore associations between maintaining a routine, and emotional and behavioural difficulties in children, using linear regression models. All eligible ALSPAC-G2 participants were sent the survey and the responders are representative of the eligible G2 population. We included measures of parental anxiety. We separately explored associations with having a keyworker parent. We used the Carey Infant Temperament Questionnaire and the Revised Rutter Parent Scale for Preschool Children to establish levels of emotional and behavioural difficulties. The measures were chosen to match previous waves in multi-generations in ALSPAC where they had been shown to be predictive of later mental health in children. The scales measure emotional and behavioural problems. Results Two hundred eighty-nine parents completed questionnaires about their 411 children. Keeping a routine was associated with emotional and behavioural difficulty scores 5.0 points lower (95% CI −10.0 to −0.1), p = 0.045 than not keeping a routine. Parents who reported keeping a routine had anxiety scores 4.3 points lower (95% CI −7.5 to −1.1), p = 0.009 than those who did not. Children of keyworkers tended to have lower emotional and behavioural difficulty scores [−3.1 (95%CI −6.26 to 0.08), p = 0.056] than children of non-keyworkers. All models were adjusted for relevant potential confounders. Conclusion Maintaining a routine may be beneficial for both child emotional wellbeing and parental anxiety, although it is also possible that lower parental anxiety levels made maintaining a routine easier. Being the child of a keyworker parent during lockdown may have been protective for child emotional wellbeing.